Latest technology for restaurant business - Bazaluk, Lidia; Bilitska, Julia (My University, 2014)
For any restaurant, point of sale technology is important. And POS restaurant software has become an important part for many restaurants. It takes a lot of time to take orders manually and then pass it on to the kitchen. With this software everything becomes as easy as the click of a button.
Keywords: меню на сенсорному екрані; управління запасами; пристрій введення і виведення; електронні касові апарати; меню на сенсорном экране; управление запасами; устройство ввода и вывода; электронные кассовые аппараты; touch screen menus; inventory management; input and output device; electronic cash registers; кафедра іноземних мов професійного спрямування